Image of church in the contemporary sacral architecture of Lithuania - Krūgelis, Linas (Journal of Architecture and Urbanism, 2012)
For many centuries, sacral architecture was conceptualised as a multiple reflection of the Catholic spiritual teaching, traditions and a symbol of particular epoch. Moreover, it served as a link between experience, knowledge and values fulfilled by of both, the present and the future man. Catholic temples, like the religion itself, were based on the mystical image of the Body of Christ (Corpus Christi). Also, it can be found not only in liturgical practices, but also in architectural expression. Up until the Second Vatican Council (also known as the Vatican II), church buildings were usually referred to as the House of God (Domus Dei), however, in the midst of the 20th century, the Church has slowly shifted to the new paradigm – the People of God (Populus Dei). Therefore, churches as buildings have also changed and became referred to as the House of God's People (Domus Ecclesiae). These essential changes were strongly expressed in the development of the 20th century sacral architecture.This article is based on the analysis of historical changes in circumstances as well as expression methods in sacral architecture and contemporary church buildings. As a method of research, the comparative analysis is used, which enables to determine impact of contemporary paradigm to the Church and sacral architecture in Lithuania.Article in Lithuanian.Bažnyčios įvaizdis šiuolaikinėje Lietuvos sakralinėje architektūrojeSantrauka. Ilgus šimtmečius sakralinė architektūra buvo suvokiama kaip daugialypis Bažnyčios mokymo, tradicijos ir esamo laikotarpio atspindys, simbolis. Tai lyg tiltas, jungiantis praeities patirtį ir žinias su dabarties ir ateities žmogiškąja pilnatve. Katalikiškos šventovės, kaip ir pati religija, rėmėsi Kristaus mistinio kūno prasme (Corpus Christi) ir simbolika tiek liturgijos apeigose, tiek architektūrinėje bažnyčios sampratoje. Iki Vatikano II Visuotinio Bažnyčios susirinkimo buvo įprasta bažnyčios pastatą vadinti Dievo namais (Domus Dei), tačiau XX a. bažnyčios paradigma radikaliai pasikeitė, Bažnyčia imama suvokti kaip Dievo tauta (Populus Dei), o pastatas – Dievo žmonių namais (Domus Ecclesiae). Šie esmingi pokyčiai itin atsispindėjo sakralinės architektūros raidoje. Straipsnyje analizuojamos istorinės pokyčių aplinkybės ir jų raiška Vakarų sakralinėje architektūroje. Naudojantis šios tyrimo dalies įžvalgomis, lyginama, kaip XX a. liturginių reformų ir bažnyčios įvaizdžio paradigmos kaita veikė šiuolaikinės Lietuvos sakralinės architektūros raidą.Reikšminiai žodžiai: sakralinė architektūra, liturginės reformos, Bažnyčia, šiuolaikinė architektūra.